INFLUÊNCIA DA ESTRUTURA ORGANIZACIONAL - ADMINISTRATIVA DAS INSTITUIÇÕES DE ENSINO SUPERIOR NO DESENVOLVIMENTO DE COMPETÊNCIAS DOCENTES PARA ATUAÇÃO NA EAD - Fernanda Roda de Souza Araújo Cassundé (Universidade Federal de Santa Catarina, 2016)
The performance of individuals working in distanc e education is influenced by several factors, but the organizational and administrative dimension of the educational institution is a key element for the development of e - skills teachers, given that both should reinforce skills as promoting conquest of new skills to enable them to know and judge for what, when and how to use ICTs in distance education. From this premise, this study seeks to answer the following question: As the development of electronic skills of teachers in higher education are related to organizational and administrative dimension of higher education institutions? Thus, a basic interpretive qualitative was conducted. Was chosen as the locus Federal University of Vale do São Francisco and as a unit of analysis, the specialization course in Public Management linked to the National Program of Public Administration (PNAP). Data collection was conducted through desk research and interviews with semi - structured. The survey results clearly show that several factors of this dimension are important for the development of electronic teaching skills and institutional policy issues need to be overcome and the frequency of training needs exist for distance education can be established in the institution.